LITERATUR REVIEW: STRES DAN KOPING PASIEN KANKER PAYUDARA SELAMA PANDEMI COVID-19 - Khairunnisa, Khairunnisa; Dewi, Yulia Irvani; Utami, Sri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
COVID-19 has had an impact on various health services, one of which has decreased the utilization of cancer health services, especially breast cancer. Breast cancer can have an impact on several dimensions for its patients, namely the physical dimension, the psychological dimension, and the social dimension. The impact of chemotherapy experienced by patients can be in the form of physical and psychological impacts. There are two forms of coping strategies, namely problem-oriented (problem-focused coping) and emotion-oriented (emotion-focused coping). Purpose: To determine stress and coping in breast cancer patients during the COVID-19 pandemic. Method: The design used is literature review. Article search based on 3 databases. Google Scholar, ScienceDirect and Pubmed, keywords in English are stress AND breast cancer OR pandemic, as well as in Indonesian include stress AND breast cancer OR the COVID-19 pandemic. Results: From the articles reviewed, 528 articles were carried out according to the inclusion criteria, 5 research articles were analyzed, namely 5 international articles. Literature review obtained the results of the age of respondents from 25-84 years as many as 528 respondents, marital status of 258 respondents (48.88%). Conclusion: The results showed that the COVID-19 pandemic greatly affected stress and coping in patients with breast cancer.